Investigating chemistry : - Johll, Matthew E. (W.H. Freeman, 2007)
The role of science to criminal investigations has inspired hit television shows and is captivating millions of people. Now there is a new chemistry book that uses a unique forensic chemistry theme to introduce basic chemical concepts to students who are not science-savvy but who must take a science course to fulfill requirements. Matthew Johll’s refreshing new approach gives students a captivating new context for learning the fundamentals of chemistry and helps them sort the facts from the fiction when it comes to the crime-solving capabilities of current chemical practice.